Manajemen Privasi Pengguna Aplikasi Kencan Daring Perempuan Semarang dalam Mengatasi Ancaman Privasi - Edvra, Paulus Angre; Hariyanto, Michelle Catarina; Zarika, Lie Tamisha (Jurnal Media dan Komunikasi Indonesia, 2025)
This qualitative multiple case study examines privacy management strategies of female users of online dating applications in Semarang, Indonesia, a region marked by increasing online dating-related crimes. Using Communication Privacy Management (CPM) theory, the research analyzes processes of privacy ownership, control, and turbulence among women aged 18–24 and 25–34. Findings indicate that users actively safeguard sensitive information such as real names, addresses, and photos, with privacy rules shaped by cultural norms, motivations, situational contexts, and risk-benefit ratio. However, even though there are regulations that control privacy, privacy turbulence is still unavoidable, including stalking, photo misuse, data theft, and unique local threats such as mystical attacks (“Semar Mesem”). Following such turbulences, participants either reinforced stricter privacy boundaries or terminated relationships, illustrating CPM’s mechanisms of rule adjustment.  This study found no significant variation between age groups in their privacy strategies. This study contributes to the limited body of Indonesian privacy research by highlighting localized risks and self-regulatory practices in online dating environments.